The impact of JPY/CNY exchange rate fluctuations on Japan's manufacturing exports to China - Li, Jifang (2025)
This study investigates how JPY/CNY exchange rate fluctuations impact Japan’s manufacturing industry exports to China. It focuses on the automotive and electronics sectors, and additional analysis is conducted on the machinery sector to explore potential heterogeneity across sectors. Employing a Difference-in-Differences (DiD) model, the analysis distinguishes between the pre-pandemic period (2018–2019) and the post-pandemic recovery phase (2023–2024) to assess asymmetric sector-level responses to exchange rate fluctuations, with the automotive sector as the treatment group and the electronics sector as the control group. By integrating macroeconomic variables, such as interest rates and the producer price index (PPI), alongside sector-specific characteristics, the study evaluates the correlation between exchange rate fluctuations, export competitiveness, and sectoral development. Although the model is designed to capture possible effects, the coefficients are not statistically significant. Findings are heterogeneous across sectors, suggesting a correlation between exchange rate fluctuations and trade behavior at both the sectoral and temporal levels. This study aims to provide policymakers and relevant business corporations with some practical suggestions on how to mitigate the correlations between JPY/CNY exchange rate fluctuations and manufacturing trade and to facilitate its stable long-term development in Japan and China.